Spatial Analysis as a predictive approach to integrating socialized rental housing in Quezon City - Espenilla, Nikko Nestor F.; Ramos, Grace C. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The challenge with socialized housing developments has always been how to generate sufficient, affordable and accessible housing for the urban poor while maintaining good proximity form city centers where utilities are easily accessible and most of the major economic activities takes place. Due to the competition for coveted urban spaces near city centers, the demand has driven cost of rent of land much higher and beyond the capacity of the lower income groups. The need for geographic advantage of good proximity to city centers has pushed the lower income group to resort to informal settlements which causes problems for the government and other sectors in Quezon City. The local government responds through a series of joint venture socialized housing project with the private sector. In order to accommodate the cost for in-city relocation and demand for limited urban spaces only home ownership type of tenure has been utilized in the program leaving costs to maintain ownership relatively high for the lower income group. The study aims to explore the potential of integrating socialized rent housing in attempt to improve housing diversity while maintaining acceptable proximities from city centers. The study utilizes spatial analysis to understand the urban structure of Quezon City and develop a predictive approach to weigh-in the potential adaptability of socialized housing. This is done through developing tools in the form of maps that utilize variables from the combination of the Bid-Rent Theory and the Theory on Space Syntax relating cost of land with accessibility and proximity from city centers. Minimum cost of land to implement different types of socialized housing projects are determined in the study. These values are used with tools developed using spatial analysis in the study to identify potential areas suitable for different types of socialized housing projects.
includes appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Rental housing -- Philippines -- Quezon City